Multiplicity of Weak Positive Solutions for Fractional p & q Laplacian Problem with Singular Nonlinearity - Dandan Yang; Chuanzhi Bai (Journal of Function Spaces)
In this paper, we prove the existence and multiplicity of positive solutions for a class of fractional p & q Laplacian problem with singular nonlinearity. Our approach relies on the variational method, some analysis techniques, and the method of Nehari manifold.